Ontario Medical Association Position Paper on Health Effects of Ground-Level Ozone, Acid Aerosols and Particulate Matter - BT Boadway; J MacPhail; C Jacobson (Canadian Respiratory Journal)
This review of the evidence of the health effects of air pollutants focuses on research conducted in Ontario. Seven key Ontario studies are cited. These findings are highly significant for people living in the Great Lakes basin (and particularly the Windsor-Quebec corridor), where high levels of certain air pollutants (eg, ground-level ozone and ultra-fine particles) occur more frequently than in other parts of Canada. The issue is a serious one, requiring an integrated and comprehensive approach by many stakeholders, including the active involvement of organized medicine. It is important that the health effects of these air pollutants are understood. Governments must act to reduce emission levels through statue and regulation bolstered by noncompliance penalties.